Effects of silica fume fineness on mechanical properties of steel fiber reinforced lightweight concretes subjected to ambient and elevated temperatures exposure - Arel, H.; Shaikh, Faiz (International Federation of Prestressing, 2018)
This paper presents the effects of silica fume (SF) fineness and fiber aspect ratios of steel fiber on fresh and harden characteristics of high-strength lightweight concrete containing oil palm shell as coarse aggregates. The effect of elevated temperatures on the residual compressive strength of above concretes is also evaluated in this study. Three different SF fineness of 18400, 21000, and 28000m 2 /kg and 2 different aspect ratios of steel fiber of 40 and 80 are considered. Results show that the increase in SF fineness and steel fiber aspect ratio marginally affect the air-dry density of steel fiber reinforced lightweight high-strength concretes, however, the workability is reduced by about 9% to 14% due to increase in SF fineness. The compressive strength of steel fiber reinforced lightweight concretes at all age increases with increase in SF fineness and an improvement of about 37% is observed at 56days by increasing the SF fineness from 18400 to 28000m 2 /kg. Strong correlations are also observed between the strength improvement factor and the SF fineness. Water absorption of above concretes is also reduced by 3% to 14% due to increase of SF fineness from 18400 to 21000 and 28000m 2 /kg. The increase of SF fineness also significantly reduces the residual compressive strength loss at 300°C and 450°C. This loss of residual compressive strength is lower in lightweight concretes containing 16mm long steel fiber than 8 mm long steel fiber. The existing Eurocode model overestimates the residual compressive strength of steel fiber reinforced lightweight concretes containing no SF, however, this discrepancy is significantly reduced with increase in SF fineness.